Framework of Architectural Marketing Capabilities in Regional Development Bank - Alam Hamdani, Nizar; Susanto, Toto; Abdul Fatah Maulani, Galih (International Journal of Engineering and Technology, 2018)
With a huge amount of assets, regional development banks have sufficient capabilities. Despite the fact that most of the capitals of the regional development banks are owned by their respective regions, it is necessary to apply appropriate marketing strategies to attract and maintain customers and ensure their satisfaction. Therefore, it is very important for them to develop architectural marketing ability in order to compete with other national banks. The present study was carried out at regional development banks in West Java using a descriptive case study design. Data were collected through in-depth interview and observation. It was revealed that was the "architectural marketing capabilities of the regional development banks were developed through a comprehensive marketing plan and based on a competition environmental analysis and marketing information. These architectural marketing capabilities can improve business performance provided that they are well-implemented.Â Â
Keywords: Architectural Marketing Capabilities; Business Performance.